T. Jackie Cuevas. Post-Borderlandia: Chicana Culture and Gender Variant Critique. New Brunswick: Rutgers UP, 2018. - Caroline E Tracey (Studies in 20th & 21st Century Literature, 2021)
Review of T. Jackie Cuevas. Post-Borderlandia: Chicana Culture and Gender Variant Critique. New Brunswick: Rutgers UP, 2018. xiii + 169 pp.
Keywords: queer; chicanx; literature